2017
DOI: 10.1073/pnas.1707186114
|View full text |Cite
|
Sign up to set email alerts
|

Caterpillars lack a resident gut microbiome

Abstract: Many animals are inhabited by microbial symbionts that influence their hosts’ development, physiology, ecological interactions, and evolutionary diversification. However, firm evidence for the existence and functional importance of resident microbiomes in larval Lepidoptera (caterpillars) is lacking, despite the fact that these insects are enormously diverse, major agricultural pests, and dominant herbivores in many ecosystems. Using 16S rRNA gene sequencing and quantitative PCR, we characterized the gut micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
347
9
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(419 citation statements)
references
References 95 publications
43
347
9
1
Order By: Relevance
“…). Interestingly, a previous study showed that the gut of caterpillars lacked any resident microbiome and was fully colonized (or invaded) by its food microbiome (Hammer et al ., ). The BG was also significantly affected by exogenous bacteria, similar to the caterpillar gut reported above.…”
Section: Discussionmentioning
confidence: 97%
“…). Interestingly, a previous study showed that the gut of caterpillars lacked any resident microbiome and was fully colonized (or invaded) by its food microbiome (Hammer et al ., ). The BG was also significantly affected by exogenous bacteria, similar to the caterpillar gut reported above.…”
Section: Discussionmentioning
confidence: 97%
“…In these studies, microbiomes composed of highly diverse taxa in low abundance have been interpreted as evidence for microbivory. In contrast, microbiome profiles showing a low diversity of highly abundant taxa are interpreted as evidence of symbiotic or pathogenic bacterial species (Hammer, Janzen, Hallwachs, Jaffe, & Fierer, ; Hubert et al., ). In this way, the prevalence–abundance patterns of the bacteria found here (Table ) suggest a combination of bacteria used as food resource (mostly environmental‐associated genera, which were more prevalent but less abundant, for example , Sphingomonas and Acinetobacter ; Table ) and of potentially symbiotic, commensalistic or pathogenic bacteria (less prevalent but much more abundant when present, for example , Bartonella , Enteroccocus; and the primary endosymbiont, Buchnera ; Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Many insects rely on microbial communities and endosymbionts to grow and develop; however, it has been shown that Lepidoptera species do not have a vertically transmitted microbial community (54,55). In addition, because the effects of microbial communities on T. ni survival and development have not been documented, we present these data only to show that microbial communities change when exposed to CECs, and not as a proven factor influencing survival.…”
Section: Discussionmentioning
confidence: 90%
“…Lactobacillaceae have been shown to act as beneficial bacteria in Drosophila (63); however, its function in T. ni is still unknown. Alcaligenaceae has been shown to be present in other moths (60), but Lepidopterans are not thought to have a functional microbiome (55). There are clear patterns regarding the changes in microbial community proportionality according to the heat map (Fig.…”
Section: Discussionmentioning
confidence: 98%